2016
DOI: 10.1007/s10661-016-5311-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of environmental and occupational exposure to heavy metals in Taranto and other provinces of Southern Italy by means of scalp hair analysis

Abstract: The monitoring of heavy metals in industrialized areas to study their association with different occupational and environmental factors is carried out in different ways. In this study, scalp hair analysis was used for the assessment of exposure to these metals in the industrial city of Taranto, characterized by a severe environmental pollution. The highest median values were observed for aluminum, barium, cadmium, lead, mercury, and uranium. Moreover, in the industrial area of Taranto, high levels of barium, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…The biological monitoring of metal pollution for human exposure is of optimal interest for researchers [ 33 ]. As a stable matrix for human bio-monitoring [ 34 ], human hair has many advantages, such as easy collection, low cost, easy transport and storage [ 35 ], and less invasive [ 36 ]. Monitoring of minor or trace elements in human hair has become an effective method for toxic trace metal exposure in recent years [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The biological monitoring of metal pollution for human exposure is of optimal interest for researchers [ 33 ]. As a stable matrix for human bio-monitoring [ 34 ], human hair has many advantages, such as easy collection, low cost, easy transport and storage [ 35 ], and less invasive [ 36 ]. Monitoring of minor or trace elements in human hair has become an effective method for toxic trace metal exposure in recent years [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Blood and urine concentrations are also widely used in the occupational settings, but the associations of elements’ concentrations in blood and urine with air are in general only observed at higher exposure levels [11]. Hair concentrations may alter as a result of hair washing frequency, smoking, dying, and may also reflect personal eating habits and nutrition profile [5,6], and given whether hair metal concentrations better reflect occupational air sampling is still disputable, metal hair concentrations should be interpreted along with air sampling data to assess occupational exposure to metals. Our findings of somewhat poor reflection of air metal concentrations, reported from the regular industrial hygiene monitoring, in hair confirm the need to combined interpretation of exposure data both from air and hair.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure data, including those from large national-wide studies, rely on various concentrations in the fume or aerosol, but may not reflect personal exposure as a function of absorption and metabolism. Studies may rely on self-reported occupational history [5] and may combine the data with blood metal samples [3], or hair concentration [6] but may provide inconsistent conclusions on the associations when compared to each other [57]. Work conditions and settings may differ to a great extent, which hampers exposure data comparison and derivation of occupational exposure limits for selected occupations in the metal industry, such as welders [8].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of this exposure yet to be studied. A study using hair of workers to assess occupational and environmental exposure to heavy metals in area of southern Italy was conducted [17]…”
Section: Resultsmentioning
confidence: 99%